Effect of Alginate-Based Edible Coating Containing Thyme Essential Oil on Quality and Microbial Safety of Fresh-Cut Potatoes - Gaowa, Saren; Feng, Ke; Li, Yuanzheng; Long, Ya; Hu, Wenzhong (Horticulturae, 2023)
Fresh-cut potatoes (Solanum tuberosum L.) are a favorite product on account of their freshness, convenience, and health benefits. However, cutting causes potatoes to lose their protective tissue and suffer mechanical damage, which greatly increases the quality deterioration and safety risk of potatoes. The background microorganism and foodborne pathogens on fresh-cut potatoes might rapidly grow during transportation, processing, and marketing, and cause high health risks for consumers. In this study, the quality and safety of fresh-cut potatoes coated with an alginate-based edible coating containing thyme essential oil (AEC-TEO) was evaluated during a storage period of 16 days at 4 °C. Samples were coated with AEC-TEO at different concentrations (0, 0.05, 0.35, and 0.65%, v/v). The quality characteristics of fresh-cut potatoes including color, weight loss, firmness, and sensory attributes were evaluated over 4 days. The viability of the background microorganism of fresh-cut potatoes and artificially inoculated bacteria involving Listeria monocytogenes (LM) was measured every 4 days. The research showed that treatment with AEC-TEO at a 0.05% concentration was the most beneficial for maintaining quality and inhibiting the microorganism of fresh-cut potatoes. The increase in L and firmness was 10.55 and 8.24 N, respectively, and the decrease in browning was 4.19 compared to that in the control. Sensory attributes represent an assessment between “indifferent” and “like a little”. The reductions in total plate counts, total coliform counts, yeast and mold counts, and Lactobacillus counts were 2.41 log cfu/g, 1.37 log cfu/g, 1.21 log cfu/g, and 2 log cfu/g, and Listeria monocytogenes decreased by 3.63 log cfu/g on fresh-cut potatoes after 16 days. Therefore, AEC-TEO effectively improved the quality of fresh-cut potatoes and, to a certain extent, prolonged their shelf life. This represents a potential application prospect for the preservation of fresh-cut potatoes.